A Dual-Labeled Multiplex Absolute Telomere Length Method to Measure Average Telomere Length - Sue Rutherford Siegel; E. Alex Calcagni; Kelsey M. Draughon; Sheree F. Logue (DNA)
Background/Objectives: Telomeres consist of repetitive nucleotide sequences and associated proteins that safeguard chromosome ends from degradation and fusion with neighboring chromosomes. As cells divide, telomeres shorten due to the end-replication problem and oxidative stress, ultimately contributing to cellular senescence. Telomeres therefore play a role in cellular health and aging. Measuring telomere length has emerged as a significant biomarker in various fields of research, including aging, cancer, and chronic diseases. Accurate measurement of telomere length is critical for interpreting research findings and clinical applications. Variability in measurement techniques can lead to inconsistent results, underscoring the need for standardized protocols. Methods and Results: The Telomere Research Network (TRN), an initiative from the National Institute of Aging and National Institute of Environmental Health Sciences, has established recommended guidelines to standardize the measurement of telomere length using qPCR to ensure accuracy and reproducibility in population-based studies. The monochrome multiplex quantitative PCR (MMqPCR) assay has emerged as a robust method endorsed by the TRN for its accuracy and reproducibility in quantifying telomere length in epidemiology ad population based studies. The absolute telomere length (aTL) qPCR assay is currently being evaluated by the TRN for its capability to utilize an oligomer standard, enabling the generation of absolute telomere lengths. The oligomer feature facilitates a more direct comparison of results across experiments and laboratories. Conclusions: This paper outlines a novel dual-labeled multiplex aTL method by incorporating dual-labeled multiplex probes to measure average absolute telomere length, providing a clear advantage over the relative telomere length assay, which quantifies the ratio of telomeric repeats to single-copy gene numbers.